Figure 10 from: Wallin H, Kvamme T, Bergsten J (2017) To be or not to be a subspecies: description of Saperda populnea lapponica ssp. n. (Coleoptera, Cerambycidae) developing in downy willow (Salix lapponum L.). ZooKeys 691: 103-148. https://doi.org/10.3897/zookeys.691.12880 - Wallin, Henrik; Kvamme, Torstein; Bergsten, Johannes (Zenodo, 2017)
Figure 10 - Aedeagi (a–d dorsal view e–f lateral view), parameres with median lobes (g–j dorsal view k–l lateral view), sclerite inside internal sac (m–n) and tergite VIII in males (o–q). a Saperda populnea populnea (Linnaeus, 1758), Joensuu, Finland b S. populnea populnea, Umeå (Västerbotten), Sweden c S. populnea lapponica ssp. n., Ljørdalen, Norway d Soppero (Lappland), Sweden e S. populnea populnea Joensuu, Finland f S. populnea lapponica ssp. n., Silkimuotka, Finland g Saperda populnea populnea (Linnaeus, 1758), Släp (Halland), Sweden h S. populnea populnea, Sillre (Medelpad), Sweden i S. populnea lapponica ssp. n., Ljørdalen, Norway j S. populnea lapponica ssp. n., Kittelfjäll (Västerbotten), Sweden; k: S. populnea populnea, Uppsala (Uppland) l S. populnea lapponica ssp. n., Enontekiö, Finland m Saperda populnea populnea (Linnaeus, 1758), Uppsala, Sweden n S. populnea lapponica ssp. n., Kiruna, Sweden o Saperda populnea populnea (Linnaeus, 1758), Uppsala, Sweden p S. populnea lapponica ssp. n., Trysil: Ljørdalen, Norway q S. populnea lapponica ssp. n., Kiruna, Sweden.